Recombinant DNA technology: revolutionizing regenerative medicine and empowering nanotechnology strategies - Lakshmi, Mallela; Dhanu, A. S.; Swamy, G. G.; Murugesan, Karthikeyan; Radhakrishnan, Anjuna; Murali, Uthamalingam; Jagannathan, S.; Elango, Boojhana; Mathanmohun, Maghimaa; Basalingappa, Kanthesh M. (Recent Research in Science and Technology, 2023)
In the past century, the concept of controlling gene expressions to enhance desirable traits in living organisms through recombinant DNA technology was merely a concept. However, in recent times, this field has made significant advancements, offering unique benefits to human life. Recombinant DNA technology allows for the safe, accessible, and abundant production of crucial proteins needed for addressing various health issues. Through laboratory methods of genetic manipulation, scientists generate recombinant DNA molecules by merging genetic material from various origins that wouldn’t naturally occur within organisms. Although the chemical structure of DNA is the same across all organisms, the nucleotide sequences vary. The application of recombinant DNA technology extends to diverse fields such as regenerative medicine, nanotechnology, and tissue engineering, allowing for the production of proteins with specific characteristics and effectiveness. This article will delve into the prevalent applications of recombinant DNA technology within fundamental research, highlighting its crucial role in contemporary endeavours across the realms of biological and biomedical sciences, particularly within the fields of regenerative medicine and nanotechnology.